The constitutionalization of international law - Klabbers, Jan.; Peters, Anne, 1964-; Ulfstein, Geir, 1951- (Oxford : Oxford University Press, 2009)
This title examines one of the most debated issues in current international law: to what extent the international legal system has constitutional features comparable to what we find in national law.
Description based on print version record.
Includes bibliographical references and index.
Keywords: International law; Constitutional law